RESPONDER: Observations of crevasses, crevasse ponding, and surface stress across west Greenland, 2017 - 2019 - Chudley, Thomas; Christoffersen, Poul (NERC EDS UK Polar Data Centre, 2021)
Datasets from the Resolving subglacial properties, hydrological networks and dynamic evolution of ice flow on the Greenland Ice Sheet (RESPONDER) project as published in the paper by Chudley et al. entitled "Controls on water storage and drainage in crevasses on the Greenland Ice Sheet". This dataset consists of remotely sensed observations of water-filled crevasses across a marine-terminating sector of the west Greenland Ice Sheet between 2017 and 2019.The dataset presented here includes all data necessary to replicate the findings presented in the main paper, including UAV photogrammetry-derived raster data (producing a series of orthophotos and digital elevation models) and observations from satellite-derived data (Sentinel-2, ArcticDEM, and MEaSUREs Greenland velocity data) of crevasse presence, water presence, and estimates of surface stress. This research was funded by the European Research Council as part of the RESPONDER project under the European Union's Horizon 2020 research and innovation program (Grant 683043). Tom Chudley was supported by a Natural Environment Research Council Doctoral Training Partnership Studentship (Grant NE/L002507/1). : Water-filled pixels were identified at a seasonal timescale using 10 m resolution Sentinel-2 data, using an NDWI threshold to classify all pixels where water was observed, using an NDWI threshold, to occur more than twice between May-October. Crevasse-filled pixels were identified from the 3 m resolution ArcticDEM, classified where residuals between 50 m smoothed and raw elevation values were greater than 1 m. UAV data were collected and processed following Chudley et al. (Cryosphere, 13, 955-968, 2019), and classified using a random forest classifier. : UAV: Custom-built Skywalker X8 fixed-wing UAV running ArduPlane autopilot software, collecting imagery with a Sony α6000 and GPS data with an Emlid Reach receiver. Images processed in Agisoft Metashape v 1.4.3. : We assign UAV-derived orthophoto and DEM data uncertainties of ±0.12 m horizontally (~1.1x the ground sampling distance) and ±0.14 m vertically (~1.3x the ground sampling distance), following Chudley et al. (Cryosphere, 13, 955-968, 2019).